The Shakespearean forest - Barton, Anne (Cambridge University Press, 2017)
Into the woods -- Staging the forest -- The wild man in the forest -- 'Like the old Robin Hood of England' -- The forest and the city -- Let the forest judge -- Afterword: Anne Barton (1933-2013) by Peter Holland
Title from publisher's bibliographic system (viewed on 30 Aug 2017)
Keywords: Shakespeare, William -- 1564-1616; Geschichte 1580-1620; Drama; Wald -- Motiv; Englisch; English drama, 17th century; History and criticism; English drama, Early modern and Elizabethan, 1500-1600; History and criticism; Forests in literature